2021
DOI: 10.1088/1741-2552/abf523
|View full text |Cite
|
Sign up to set email alerts
|

A machine-learning algorithm correctly classifies cortical evoked potentials from both visual stimulation and electrical stimulation of the optic nerve

Abstract: Objective. Optic nerve’s intraneural stimulation is an emerging neuroprosthetic approach to provide artificial vision to totally blind patients. An open question is the possibility to evoke individual non-overlapping phosphenes via selective intraneural optic nerve stimulation. To begin answering this question, first, we aim at showing in preclinical experiments with animals that each intraneural electrode could evoke a distinguishable activity pattern in the primary visual cortex. Approach. We performed both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The dimensionality reduction and clustering of the EEPs were automatic and relatively assumption-free [31], enabling a straightforward classification of significant EEP without defining a priori punctual features, such as latency or amplitude. Indeed, we already showed that punctual features appeared to be not informative enough for prediction models [17]. Hence, this classification allowed us to compare how significant electrically evoked responses spread across the cortex with changing stimulus parameters and electrode configuration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dimensionality reduction and clustering of the EEPs were automatic and relatively assumption-free [31], enabling a straightforward classification of significant EEP without defining a priori punctual features, such as latency or amplitude. Indeed, we already showed that punctual features appeared to be not informative enough for prediction models [17]. Hence, this classification allowed us to compare how significant electrically evoked responses spread across the cortex with changing stimulus parameters and electrode configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments were performed according to the authorisation GE519 approved by the Département de l’Emploi, des Affaires Sociales et de la Santé, Direction Générale de la Santé of the Republique et Canton de Genève (Switzerland), as previously described [17]. Two female Chinchilla Bastard rabbits (>16 weeks, >2.5 kg) were premedicated 30 min before the transfer to the surgical room with an intramuscular injection of xylazine (3 mg kg -1 ; Rompun®20 mg ml -1 , 0.15 ml kg -1 ), ketamine (25 mg kg -1 ; Ketanarkon ® 100 mg ml -1 , 0.25 ml kg -1 ) and buprenorphine (0.03 mg kg -1 ; Temgesic® 0.3 mg ml -1 , 0.1 ml kg -1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Essentially, artificial vision is a rudimentary form of vision caused by the artificial activation of neurons in the visual system by physical forces such as mechanical, chemical or electrical stimuli. For example, visual prostheses electrically stimulate visual neurons upstream to the damaged location, such as the retina, the optic nerve, the lateral geniculate nucleus or the cortex [5,[12][13][14][15][16][17][18][19][20][21]. The artificial stimulation of visual neurons induces the perception of bright dots in the visual space (called phosphenes).…”
Section: Artificial Visionmentioning
confidence: 99%